Examining the effects of openings at the base of slender reinforced concrete (tilt-up) wall panels subjected to varying wind pressures - Cook, Andrew (Kansas State University, 2011)
This report examines the effects of openings located at the base of reinforced concrete slender wall panels (tilt-up panels) designed in accordance with the American Concrete Institute (ACI) Committee 318-11 Building Code Requirements for Structural Concrete Section 14.8 Alternative Design of Slender Walls. The parametric study calculates the reinforcement (longitudinal) required for specific panels in accordance with ACI 318-11 Section 14.8 and compares the designs to a finite element analysis conducted with SAP 2000 version 14 to determine the appropriateness of the assumptions made in Section 14.8. Furthermore, this report compares the design of a tilt-up panel designed by Section 14.8 Alternative Design of Slender Walls and designed by Section 10.10 Slenderness Effects in Compression Members.
Keywords: Slender reinforced concrete wall panels; Tilt-up; Finite element methods; Architectural engineering (0462); Civil Engineering (0543); Engineering (0537)